منهج النبي (ص) في التعامل مع المخطئ : دراسة تحليلية - إسلام، محمد فخر
This research aims to analyse the topic of “The Prophet’s (SAW) Approach in Dealing with the Wrong Doer” because the researcher did not see a recent study that dealt with the subject in its aspects, although it is a living problem that requires a study that suits the current era. The goal of this research is to explain the methodological fundamentals of the mentioned topic based on the available books of the Sunnah biographies. The study was divided into four chapters that included the definition of the mistakes, showing the methods of the Prophet (SAW) on how to deal with the wrong doer, and the duties of Islamic preachers on how to deal and fix such mistakes. The study was subjected to two approaches, inductive and analytical. The researcher has reached sixty-eight (68) approaches as a result of this research, the most important of them: Everyone who is taking a responsible position should follow the guidance of the Prophet (SAW) on how to fixing mistakes and mainly focusing on wisdom, good advice, positive response, advice for righteousness, having mercy, explaining the consequences of doing wrong things, and providing the right alternative.